Extreme heterogeneity in populations of vesicular stomatitis virus. - Steinhauer, D A (1989)
Vesicular stomatitis virus (VSV) sequence evolution and population heterogeneity were examined by T1 oligonucleotide mapping. Individual clones isolated from clonal pools of wild-type Indiana serotype VSV displayed identical T1 maps. This was observed even after one passage at high concentrations of the potent viral mutagen 5-fluorouracil. Under low-multiplicity passage conditions, the consensus T1 fingerprint of this virus remained unchanged after 523 passages. Interestingly, however, individual clones from this population (passage 523) differed significantly from each other and from consensus sequence. When virus population equilibria were disrupted by high-multiplicity passage (in which defective interfering particle interference is maximized) or passage in the presence of mutagenic levels of 5-fluorouracil, rapid consensus sequence evolution occurred and extreme population heterogeneity was observed (with some members of these population differing from others at hundreds of genome positions). A limited sampling of clones at one stage during high-multiplicity passages suggested the presence of at least several distinct master sequences, the related subpopulations of which exhibit at least transient competitive fitness within the total virus population (M. Eigen and C.K. Biebricher, p. 211-245, in E. Domingo, J.J. Holland, P. Ahlquist, ed., RNA Genetics, vol. 3, 1988). These studies further demonstrate the important role of selective pressure in determining the genetic composition of RNA virus populations. This is true under equilibrium conditions in which little consensus sequence evolution is observed owing to stabilizing selection as well as under conditions in which selective pressure is driving rapid RNA virus genome evolution.